Exploration of Stakeholder Perceptions on the Application of Biomining for Mining Waste Management - Rafiuddin (Journal of Renewable Engineering, 2025)
Mining waste management is a major challenge, resulting in water pollution, ecosystem degradation, and heavy metal accumulation. Biomining, the use of microorganisms to extract and stabilize metals, is seen as an innovative solution that is more environmentally friendly than conventional methods. This study aims to explore the perceptions of stakeholders regulators, mining companies, local communities, and academics on the application of biomining in mining waste management. The study employed a descriptive qualitative approach with a case study design. Data were obtained through in-depth interviews, focus group discussions, field observations, and document reviews. Analysis was conducted manually through transcription, coding, theme grouping, and source triangulation to ensure data validity. The results show that academics and regulators have positive perceptions of biomining because it supports the principles of a circular economy and sustainable development. Local communities welcome biomining with cautious optimism, influenced by negative experiences with conventional methods, but still demand transparency and safety assurance. Conversely, mining companies are more skeptical, considering technical risks, initial investment costs, and the uncertainty of long-term profitability. The study's conclusions emphasize that the success of biomining depends on convincing technical evidence, regulatory certainty, and social legitimacy through community engagement. Triple helix synergy between government, industry, and academia is needed to accelerate the adoption of biomining technology in Indonesia.